CLIL Teachers Training Needs: Myanmar Upper Secondary School Biology Teachers’ Voices - Htay, Sandar; Ngonkum, Sutida (Journal of Humanities and Social Sciences (HUSOKKU), 2023)
Abstract This qualitative study investigated the needs of school teachers teaching biology subjects at the upper-secondary level in Myanmar for the CLIL teacher training. Semi-structured interview was conducted through the online interview asking four upper secondary biology teachers about their 1) current teaching practices, 2) problems in the current teaching, and 3) needs in CLIL teacher training. Findings revealed that in terms of their current teaching practices, most teachers used the teaching methods that facilitate students’ knowledge gaining. In revealing teachers’ problems, data indicated that they encountered difficulties in areas of teaching methodology, content knowledge, English language for communication, thinking skills, learning activities, assessment, and classroom management. In terms of teachers’ needs, the four teachers wanted the training course to develop their 1) skills and knowledge in CLIL teaching, 2) linguistic knowledge necessary for their teaching content, 3) overall language knowledge and skills, and 4) knowledge of how to manage activities to help their students learn successfully. Keywords: Content and Language Integrated Learning (CLIL), Needs Analysis (NA), teacher training, upper secondary school teachers in Myanmar